Language attitudes among urban Moroccan youth following recent developments in - Abdullah, Rashid (AUC Knowledge Fountain, 2018)

(untitled)
This study explores the important and complex relationship between language attitudes, language policy (LP) and linguistic landscape (LL) (Spolsky, 2004; Shohamy 2006). In 2011, following the Arab Spring and the shockwaves it created in the region, a referendum on constitutional reforms was held in the Kingdom of Morocco. The reforms led to the recognition of the Tamazight language as an official state language, making Morocco the first nation to do so in North Africa. The Tamazight language and the Tifinagh script have become ubiquitous in major cities, particularly in the national capital, Rabat. This study surveyed and interviewed urban Moroccan youth in Rabat regarding their attitudes toward the recent changes in language policy and the alterations in their linguistic landscape. The youth were especially chosen for this study because of their ability to indicate future trends and inspire new linguistic paradigms. Previous studies into language attitudes in North Africa have mainly focused on competition between French and Arabic (Bentahila, 1983; Chakrani, 2010) and none has incorporated the element of linguistic landscape and its ability to alter attitudes and perceptions (Landry & Bourhis, 1997). This study primarily focuses on attitudes toward Tamazight, but also investigates attitudes toward English, French, Modern Standard Arabic (MSA) and Moroccan Arabic (MA). Findings from the study show what appear to be a softening of negative attitudes toward Tamazight and may even signal a positive evolution of general attitudes among the urban youth population toward the indigenous language, further proving the theory that an individual’s surroundings and environment impact their attitudes and perceptions over time (Shohamy, 2006).